L'Etat britannique et la crise en Irlande du Nord : de Wilson à Thatcher - Philippe Cauvet (Revue Française de Civilisation Britannique)
This paper analyses the successive British governments' action in Northern Ireland from 1968 through the seventies. It shows that in this period, London's action was marked by its sometimes passive, sometimes active alliance with the Northern Irish unionist bloc. The first section shows that until the election of Margaret Thatcher as Prime minister, the central government's action was defined by its refusal to confront the unionist majority in Northern Ireland, which makes this period a specific phase of governmental action in the 30 years of conflict. The second section demonstrates that this alliance resulted in the limited effectiveness or even failure of London's action in the field of law and order. The third section compares the 1973 Sunningdale initiative and the 1985 Anglo-Irish Agreement showing that the failure of Sunningdale can also be explained by London's dependence on Northern Irish unionist forces.